2018
DOI: 10.1016/j.enconman.2018.08.086
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and sensitivity analysis of energy assessment for office buildings based on Dempster-Shafer theory

Abstract: Uncertainty and sensitivity analysis of building energy has become an active research area in order to consider variations of input variables and identify key variables influencing building energy. When there is only limited information available for uncertainty of building inputs, a specific probability for a given variable cannot be defined. Then, it is necessary to develop alternative approaches to probabilistic uncertainty and sensitivity analysis for building energy. Therefore, this paper explores the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Instead, in this study we used a validated grey-box dynamic model [53,54] to perform multiple simulation runs in a reduced time frame. Indeed, grey-box models are very flexible and can be used in the inverse mode to estimate lumped properties of the actual building, eventually extending their applicability with Bayesian analysis [55,56] or Dempster-Shafer theory of the evidence [57]. In this case, the original building design configuration was considered as a baseline.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, in this study we used a validated grey-box dynamic model [53,54] to perform multiple simulation runs in a reduced time frame. Indeed, grey-box models are very flexible and can be used in the inverse mode to estimate lumped properties of the actual building, eventually extending their applicability with Bayesian analysis [55,56] or Dempster-Shafer theory of the evidence [57]. In this case, the original building design configuration was considered as a baseline.…”
Section: Methodsmentioning
confidence: 99%
“…In BPA, SA has been applied to investigate different types of modelling outputs: total energy demand [9], peak electricity loads [12], cooling and heating demand [9,25], carbon emissions [26] and overheat frequency [27]. For example, De Wilde et al [27] has identified that lighting and equipment gains are the key factors for the annual electricity demand for cooling in office buildings.…”
Section: Sensitivity Analysis To Assess Building Energy Performancementioning
confidence: 99%
“…Hopfe & Hensen, 2011;Struck, 2012;Struck, Jan Hensen, & Kotek, 2009). Furthermore, the uncertainty in the external factors also results in uncertain prediction such as microclimate (Sun et al, 2014), macroclimate (Tian, de Wilde, Li, Song, & Yin, 2018) and economic parameters (Rysanek & Choudhary, 2013). Heeren et al (2015) has studied several internal and external factors which influences the environmental impact of buildings and ranked climate change, electricity mix, ventilation rate, heating system and construction material as highly influential factors (Heeren et al, 2015).…”
Section: Uncertainty / Sensitivity Analysis Of Building Energy Models 22mentioning
confidence: 99%